2021
DOI: 10.1002/anie.202106250
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Dehydrating Bimodules in trans‐Acyltransferase Polyketide Biosynthesis: A Showcase Study on Hepatoprotective Hangtaimycin

Abstract: A bioassay‐guided fractionation led to the isolation of hangtaimycin (HTM) from Streptomyces spectabilis CCTCC M2017417 and the discovery of its hepatoprotective properties. Structure elucidation by NMR suggested the need for a structural revision. A putative HTM degradation product was also isolated and its structure was confirmed by total synthesis. The biosynthetic gene cluster was identified and resembles a hybrid trans‐AT PKS/NRPS biosynthetic machinery whose first PKS enzyme contains an internal dehydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“… Xiao et al, 2019 ). Stress, excessive diet, alcohol and drugs abuse can cause liver injure, which may further develop into chronic fatigue, coagulopathy, liver failure and even cancers ( Luo et al, 2021 ). Liver diseases which develop from liver injury have brought enormous burdens for society and economics.…”
Section: Introductionmentioning
confidence: 99%
“… Xiao et al, 2019 ). Stress, excessive diet, alcohol and drugs abuse can cause liver injure, which may further develop into chronic fatigue, coagulopathy, liver failure and even cancers ( Luo et al, 2021 ). Liver diseases which develop from liver injury have brought enormous burdens for society and economics.…”
Section: Introductionmentioning
confidence: 99%
“…On the right end of the cluster downstream of the trans -AT gene htm10 , the htm11 gene encodes a cytochrome P450 monooxygenase. An essential role for HTM biosynthesis was verified for the htm10 homologous gene htmA7 in S. spectabilis CCTCC M2017417 . HTM production was abolished in the htm11 deletion mutant (Htm11KO), but TDD was detected at levels similar to the wild-type strain, indicating that an HTM biosynthetic intermediate bearing the TDD moiety was produced in the Htm11KO (Figures D and A).…”
mentioning
confidence: 99%
“…The cluster encodes six NRPS modules, two in PKS/NRPS hybrid Htm2 and four in NRPS Htm4 and 5 (Figure A, Table S3). A ClusterBlast analysis against the antiSMASH database indicated that the htm cluster was present and conserved in some S. spectabilis strains, although the gene arrangement and size differed slightly from the htm cluster in S. spectabilis CCTCC M2017417 (Figure S1). To confirm the htm cluster and to identify its boundaries, six genes in or flanking the region of the cluster were inactivated in S. spectabilis CPCC 200148 by gene knockout (Figures S2–S7).…”
mentioning
confidence: 99%
See 2 more Smart Citations